2020
DOI: 10.1007/s13524-020-00855-x
|View full text |Cite
|
Sign up to set email alerts
|

Fertility History and Biomarkers Using Prospective Data: Evidence From the 1958 National Child Development Study

Abstract: Research on the later-life health implications of fertility history has predominantly considered associations with mortality or self-reported indicators of health. Most of this previous research has either not been able to account for selection factors related to both early-life and later-life health or has had to rely on retrospectively reported accounts of childhood circumstances. Using the 1958 National Child Development Study, and in particular the biomedical survey conducted in 2002-2003, we investigate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 70 publications
3
16
1
Order By: Relevance
“…Retrospectively collected information may be of lower quality than prospectively collected information (cf. Sironi et al, 2020 ) because it may be prone to recall bias. In a recent study, in which prospective and prospective data on British people in their 50s were compared, no systematic differences in the distribution of important early-life characteristics (socioeconomic position of father when growing up and parental separation between birth and age of 16 years) were found, but the authors noted that retrospectively collected early-life characteristics were slightly, but statistically significantly, more strongly associated with later-life health than were prospectively collected early-life characteristics ( Jivraj et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Retrospectively collected information may be of lower quality than prospectively collected information (cf. Sironi et al, 2020 ) because it may be prone to recall bias. In a recent study, in which prospective and prospective data on British people in their 50s were compared, no systematic differences in the distribution of important early-life characteristics (socioeconomic position of father when growing up and parental separation between birth and age of 16 years) were found, but the authors noted that retrospectively collected early-life characteristics were slightly, but statistically significantly, more strongly associated with later-life health than were prospectively collected early-life characteristics ( Jivraj et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the nonlinear effects of fertility on health ( Högnäs et al, 2017 ), number of children was coded as a categorical variable, with categories of 0, 1, 2, 3, and 4+ children (cf. Grundy et al, 2019 ; Sironi et al, 2020 ). Respondents’ educational attainment was coded according to their highest educational qualification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Against the background of population aging and demographic changes occurred in the past decades, the extent to which fertility and partnership behaviors produce long-term consequences on subjective wellbeing at older ages is increasingly of concern. Within the life course framework, it has been theorized that older adults' health and subjective wellbeing (SWB) are influenced by events and experiences occurred throughout the different life stages (Barker 2004;Ben-Shlomo and Kuh 2002;Carr and Utz 2020;Hayward and Gorman 2004;Kuh et al 2018;Pudrovska and Anikputa 2014;Umberson and Thomeer 2020) and a spate of studies have reported substantial effects of fertility and partnership histories on health, healthy behaviors and mortality (Barclay et al 2016;Grundy and Tomassini 2010;Grundy and Kravdal 2010;Grundy and Holt 2000;Hank 2010;Quashie et al 2021;Reczek et al 2016;Sironi 2019;Sironi et al 2020). Part of this literature adopted a holistic approach to the analysis of family histories by accounting for both occurrence and timing of fertility and partnership events (e.g., Barban 2013;Kravdal et al 2012;O'Flaherty et al 2016;Sabbath et al 2015), thus recognizing the dynamic interdependencies among these processes (Macmillan and Copher 2005).…”
Section: Introductionmentioning
confidence: 99%
“…While some studies did not nd any relationship between birth numbers and women's later life health [3]. Besides, having children at a very young age is detrimental to women's later life health, as well as late childbearing [4,5]. Research showed that risk enhancement from delayed childbirth with regard to cardiovascular disease, especially diabetes, hypertension, and congestive heart failure [6].…”
Section: Introductionmentioning
confidence: 99%